ANALISIS BIAYA-MANFAAT PADA PROYEK PENINGKATAN RUAS JALAN PROVINSI Studi Kasus : Ruas Jalan Wonosari-Semin Kabupaten Gunungkidul - , Yuli Nurwahyu Dewi ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The objective of highway transportation arrangement and development was to provide a reliable highway facility under the following criteria namely the establishment of sufficient performance level and the low transportation cost in order to balance the growth of vehicle numbers and to create an efficient and effective transportation system. In relation to the matter, the roads of WonosariSemin should have been improved in order to have better performance and to provide more benefits for the users. However, the road widening demanded big cost. Therefore, there should be a review in order to consider whether the cost that should be expended for the improvement of the roads of Wonosari-Semin would be in line with the benefits that the users would have or not in addition to the period of usage. The research was to evaluate the performance of the road of Wonosari-Semin, to identify and to analyze the benefits of the improvement in the roads of WonosariSemin by Benefit Cost Ratio (BCR) in the project of improving the roads of Wonosari-Semin. The research on the project of improving the roads of Wonosari-Semin had several stages. Then, the data in the research consisted of the primary data and the secondary data. The data was attained from the institutional survey and the field survey. The results of the research showed that the saturated degree for the roads of Wonosari-Semin was lower than 0.75 and was still under the requirements of MKJI 1997. In other words, the researcher would like to state that the saturated degree in the roads was still low and did not experience any problem in terms of capacity. Then, from the feasibility value that was measured by calculating the total benefit in the form of operational cost saving and of time value saving in comparison to the investment cost, the researcher found that the saturated degree was 3.85. As a result, the improvement on the roads of Wonosari-Semin was feasible to be implemented.